Controle e repressão aos Waimiri-Atroari na fronteira Amazonas-Roraima no período da ditadura Brasileira (1964-1985): uma faceta da parceria entre estado e o mundo empresarial (Paranapanema-Sacopã) - Santos, Adriana Gomes (2021)
The research focused on the analysis of the action performed by the Paranapanema Group in connection with the business-military dictatorship in the process of appropriation of the Waimiri-Atroari indigenous territory, between 1964 and 1985. This Group, with the support of the paramilitary company Sacopã, in mutual agreement with the public authorities, carried out intrusion on and eviction from the indigenous territories for mineral production. From the analysis of the sources’ immanence, the constitutive nexuses revealed Paranapanema in its entirety - capital, partners, economic areas of activity, mineral production - the mechanisms of territorial appropriation engendered through the relations established between the business sector and the military that took over the power after the 1964 coup and that worked through the intricacies of the public machine. This process was forged as part of the political option of the business-military Dictatorship, for national development, which not only maintained the structural forms of dependence of our economy on international capital, but deepened its subjection. The political-economic project of occupation of the Amazonia engendered by the business-military Dictatorship was justified by the narrative on the need to integrate into national development a space that was characterized by a demographic vacuum. In other words, the different ethnic groups and countless traditional communities, inhabitants of the region since immemorial times, were once again taken as “non-beings”, nonexistent, as the conquerors' booklets read at the beginning of colonization. The numerous documents extracted from the SNI (Information National Service then the Intelligence Agency) archives, regional archives, CPI (Parliamentary Commission of Inquiry) reports, among others, prove that this policy resulted in the near extermination and/or social disintegration of these indigenous communities, which, expelled from their lands, forcibly removed, or subjected to inhumane conditions of survival, to degrading work imposed by agents of intrusion into their territories, by individuals and private companies, among them Paranapanema